The Role of Estrogen in the Development of Breast Cancer - Massardi, Nikki Aldi (Biomedical Journal of Indonesia, 2021)
Breast cancer is a hormone-dependent disease that relies on the mitogenic effect ofestrogen to increase tumorigenesis and tumor growth. Clinically significant levels ofestrogen-Î± receptor (ERÎ±) expression are seen in 80% of human breast cancers,whereas progesterone receptor is expressed in 55% of human breast cancers. Thesedata are one of the bases for the development of endocrine therapy. Endocrinetherapy is therapy that targets the pathway and synthesis of estrogen, by blocking itvia receptors, reducing circulating levels of estrogen, or suppressing estrogensynthesis in the tissues of women diagnosed with breast cancer.